"Forever Young: Consumer Culture and the Ageing Body in Hanif Kureishi’s “The Body”" - Oró Piqueras, Maricel (Miscelánea: A Journal of English and American Studies, 2007)
Contemporary British society is growing older and older. However, the blind veneration for the youthful and beautiful body, reflection of a range of good personality attributes, is becoming more and more equivocal. Whereas the industrial revolution contributed to the undermining of the social and cultural status of those reaching old age, a contemporary society based on a postmodernist ideology and consumerist culture seems to give an opportunity to those who keep the signs of age at bay from their bodies with the use and abuse of rejuvenatory products and techniques. In this paper, I aim to analyse the contradictions existing in relation to the conceptions of the young and old body and, by extension, of youth and old age in contemporary British and contemporary Western society by analysing Hanif Kureishi’s short story “The Body.” Kureishi pushes such contradictions to an extreme by presenting a surrealist story in which a desire to remain young forever merges with the need to keep one’s sense of self and identity within a community that is increasingly changing ethics for aesthetics.
Keywords: Ageing process; Consumer culture; The cult of youth; External appearance; Western society